Building Bridges Between Cultures: The Originalities of the Portuguese Tile - Magalhães, Fernando (European Scientific Journal, ESJ, 2020)
Tile was introduced in the Iberian Peninsula by Muslims, who occupied it from the 8th century ahead, following the Muslim invasions. This material has become a striking element of the centre and south Spanish culture. However, its introduction and dissemination in the present Portuguese territory occurred only in the sixteenth century, more specifically in the D. Manuel I Reign. Not being a Portuguese creation, but resulting from multiple contacts and cultural crossings, the tile was not only absorbed by the local culture, but also taken by the Portuguese people to other places, such as Brazil or India. In these new places, it acquired new meanings, being adapted and transformed according to the local aesthetic tastes. The tile acquired a maximum expression in Portugal as a decorative element narrating, at the same time, events of the Portuguese society and culture. It has been used extensively over five centuries and has been adapted to the local spatiotemporal circumstances, being created in innovative and aesthetic forms. The tile, starting as a decorative element inside palaces, manor houses, churches and convents, would eventually become a material for facade cladding of public and private buildings. This represents panoramas of an abstract geometry and also events of the local life. In the 21st century, tile has acquired new symbolic values in the representation of the community to the tourist audience.